Catalytic Amine Oxidation under Ambient Aerobic Conditions: Mimicry of Monoamine Oxidase B1. Issue 31 (18th June 2015) - Murray, Alexander T.; Dowley, Myles J. H.; Pradaux‐Caggiano, Fabienne; Baldansuren, Amgalanbaatar; Fielding, Alistair J.; Tuna, Floriana; Hendon, Christopher H.; Walsh, Aron; Lloyd‐Jones, Guy C.; John, Matthew P.; Carbery, David R.
Abstract The flavoenzyme monoamine oxidase (MAO) regulates mammalian behavioral patterns by modulating neurotransmitters such as adrenaline and serotonin. The mechanistic basis which underpins this enzyme is far from agreed upon. Reported herein is that the combination of a synthetic flavin and alloxan generates a catalyst system which facilitates biomimetic amine oxidation. Mechanistic and electron paramagnetic (EPR) spectroscopic data supports the conclusion that the reaction proceeds through a radical manifold. This data provides the first example of a biorelevant synthetic model for monoamine oxidase B activity.